1987
DOI: 10.1038/326515a0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin/PCNA is the auxiliary protein of DNA polymerase-δ

Abstract: Identification of the cellular proteins whose expression is regulated during the cell cycle in normal cells is essential for understanding the mechanisms involved in the control of cell proliferation. A nuclear protein called cyclin of relative molecular mass 36,000 (Mr 36K), whose synthesis correlates with the proliferative state of the cell, has been identified in several cell types of human, mouse, hamster and avian origin. The rate of cyclin synthesis is very low in quiescent cells and increases several fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
706
1
19

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,702 publications
(751 citation statements)
references
References 26 publications
18
706
1
19
Order By: Relevance
“…49,50 More profound suppression of cancer cell proliferation activity in the PDT with anticancer drugs group than in the PDT alone was observed. Song et al 51 reported that leukotrienes and cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 More profound suppression of cancer cell proliferation activity in the PDT with anticancer drugs group than in the PDT alone was observed. Song et al 51 reported that leukotrienes and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…18 The administered solution was incubated at 37°C for 3 hours, later decantated and then washed three times in PBS. To induce LD 50 PDT conditions, a laser power of 12 J/cm 2 was chosen to irradiate the NOZ cells. The laser was irradiated for 1 minute.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…PCNA is fundamental to nuclear DNA replication, acting as a sliding clamp that tethers the leading strand DNA polymerase d to its template, enhancing the enzyme's processivity (Prelich et al, 1987;Bravo et al, 1987;Krishna et al, 1994). In addition, PCNA is required for nucleotide excision repair (Shivji et al, 1992;Nichols and Sancar, 1992) and is involved in one pathway of base excision repair (Matsumoto et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is normally localized in the nucleus as an essential component of the replication mechanism (Bravo et al, 1987;Prelich et al, 1987). Besides its role in replication, it is directly involved in nucleotide excision repair (Shivji et al, 1992), and elevated expression is detected in response to DNA damage in vivo (Hall et al, 1993).…”
Section: Discussionmentioning
confidence: 99%